PREFERENSI PANELIS PADA TIGA KLON KENTANG TERHADAP KULTIVAR GRANOLA DAN ATLANTIK - gunarto, anton (Jurnal Sains dan Teknologi Indonesia, 2012)
The research objective was to determine the preferences panel of three clones of potato seed tubers G1 namely A5, PAS3063, PAS3064 and Granola and Atlantic cultivars as comparison varieties, as well as to determine levels of starch, sugar and water content. Based on the results of Kruskal Wallis test for flavor and texture parameters on the tuberswere not significantly different cooking shows, while the aroma and color were significantly different between clones / cultivars. Panelists on the test results for the parameters of boiled tubers taste, texture, aroma and color looks significantly different between clones / cultivars. Analysis of variance was significantly different levels of tuber starch content, sugar contentand moisture content. Gerombol analysis based on the preferences panel of taste, texture, aroma and color in fried and boiled potatoes indicate that the resemblance is closer to A5 Granola with similarity percentage of more than 54.76% and Atlantic closer resemblance to the PAS3063 and PAS3064 with similarity percentage of more than 77.38% .